The secret of the old clock ebook 80th anniversary limited edition. - Keene, Carolyn (Nancy Drew, 2009)
Read the original Nancy Drew mystery, the first book in the iconic mystery series that introduced readers to America's favorite teenaged sleuth! The accidental rescue of a little girl who lives with her two great-aunts leads to an adventurous search for a missing will. Longtime fans and aspiring detectives alike will enjoy solving the case alongside Nancy Drew in this suspenseful, action-packed thriller.